The Intertextual Dimension of Otherness in Jhumpa Lahiri’s The Namesake - Chifane, Liviu Augustin (Journal of History Culture and Art Research, 2015)
The Intertextual Dimension of Otherness in Jhumpa Lahiri’s The Namesake Abstract The work of the Pulitzer prize winner Jhumpa Lahiri has been referred to as a solid representation of diaspora and immigrant literature. One of her most famous books, the novel The Namesake (2003), illustrates the experience of dislocation psychologically exploring the identity crisis and the sense of alienation. Nevertheless, the novel offers the opportunity of a trans-textual approach that leads to a philosophical vision of the traditional issues of alterity. The aim of the paper is to explore the extent to which an intertextual reading of the novel can provide a better understanding of the multitude of socio-cultural and identity questions the book raises. The resonance of Nikolai Gogol’s name, work and tumultuous existence transgresses the pages in layers of meaningful interpretation of Otherness as a duality of name and cultural affiliation. The never read essential text, Gogol’s short story The Overcoat, shapes the tragic paternal imagery in a continual struggle of the inner self to clarify the sense of displacement and hybridity.